Scientists in Search of Their Conscience
XIV, 232 p.
Keywords: "Scientists in Search of Their Conscience" is the edited proceedings of the European Symposium on the effects of science on society held in Brussels in 1971. Organised by The European Committee of The Weizmann Institute, Israel, the Conference gave scientists from varied disciplines and many countries the platform from which to explore in depth the dilemma facing them. The dilemma is the responsibility of scientists for society's use of scientific findings. Though no hard and fast conclusions were reached-in fact quite the contrary-the discussions left no doubt that scientists were becoming aware that they can no longer claim that the pursuit of knowledge is divorced from its use. Yet should they begin to face the responsibility for the application of their work, it is clear that their freedom will be impaired. The loss of freedom is of course part of the dilemma of science. Contents Official Opening, Monday, June 28, 1971 1 Chairman: Albert B. Sabin 3 Speakers: Theo Lefevre . 7 Altiero Spinelli . 11 Morning Session, Monday, June 28, 1971 13 Chairman: John C. Kendrew 15 Speakers: Friedrich Cramer "Can our Society meet the Challenge of a Technological Future?" . . . 19 Aharon Katzir-Katchalsky "A Scientist's - proach to Human Values" . 33 Discussion. . . . . . . . . . . . . . . . . . . . . 46 Afternoon Session, Monday, Jtme 28, 1971 . . . . . . . . 61 Chairman: Hendrik B. G. Casimir . . . . . . . . . . 61 Speakers: Leon Van Hove" Physical Science in Relation to Human Thought and Action" . . . . . . 63 Chaim L. Pekeris "The Impact of Physical Sciences on Society" 73 Discussion. . . . . . . . . . . . . . . . . . . . .